Optimalization of Equilibration and Thawing Methode on Freezing Process of Garut Ram Semen (Ovis aries) - Herdis, Herdis; Toelihere, MR; Supriatna, I; Purwantara, B; Adikara, RTS (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2005)
Generally, the problem of semen freezing process is cold shock effect and intracelullar change due to water release which is related to ice crystal formation. One factor to solve the problem is finding out optimal equilibration time and thawing method so there is only a little damage spermatozoa during freezing process. The research has been done to explore the influence of equilibration time and thawing methode on frozen semen quality of garut rams. The results shown that the mean of percentages of progressive motile sperm, percentages of viable sperm, percentages of plasma membrane and acrosomal intact on four hours equilibration (52.50% ; 62.33%; 57.17% and 56.42%) were not significantly different (P>0.05) from five hours equilibration (52.27%; 63.67%; 56.92% and 57.58 %) and six hours equilibration (54.17%; 61.00%; 59.42% and 58.58%) respectively. The percentages of progressive motile sperm, percentages of viable sperm, percentages of plasma membrane and acrosomal intact on the thawing method on the temperature of 370C for 30 seconds (53.33% ; 62.39%; 57.94% dan 58.61) were not significantly different (P>0.05) from the thawing methode on the temperature of 250C for 45 seconds (52.22% ; 62.28%; 57.72% dan 56.44) respectively. The conclusion shown that the treatment of four hours equilibration, five hours equilibration, six hours equilibration and also the treatment of thawing method on the temperature of 370C for 30 seconds and the thawing methode on the temperature of 250C for 45 seconds do not have effect on garut ram freezing semen quality. (Animal Production 7(2): 74-80 (2005) Key Words : Equilibration, Thawing, Semen, Garut ram